Predictive mechanisms in passive and active touch - Jeschke, Michaela; Justus Liebig University Giessen (My University, 2025)
Perception is an active process which is shaped by prior sensory experiences and expectations about the objects and situational demands that an agent is confronted with. The first part of this work focuses on neural adaptation processes in passive tactile perception, while the second part will examine the role of prior visual information and different context factors for optimization of active haptic explorations. In the first study we exploited tactile adaptation aftereffects to reveal previously unknown communalities in the somatosensory processing of spatially structured tactile features. Two-point distance, macro-scale roughness, and curvature have been extensively studied in isolation in the past and are deemed critical for shape and material perception. Their potential overlap in sensory processing however had remained unexplored. Across four experiments, we here demonstrate that adaptation to one property can produce aftereffects in the perception of the other properties: For roughness and tactile distance specifically, cross property aftereffects were bidirectional, specific to orientation and skin region, weaker than the respective within-property aftereffects, and did not result from peripheral receptor fatigue. Together, the results suggest a common neural substrate for processing spatially structured tactile features at early cortical levels, providing a window into how low-level spatial features may be organized to support coherent object perception. A second study compliments the first one: here, we investigated whether there is a relationship between biophysical skin properties with basic tactile abilities and the tactile distance aftereffect. While previous studies clearly demonstrated that peripheral factors are not the origin and cause of tactile aftereffects, it had remained unclear whether they could have an additional impact on aftereffect expression, possibly explaining interindividual differences in e.g. the aftereffect strength. Results revealed that higher hydration and elasticity were related to increased tactile sensitivity and spatial acuity. The magnitude of distance aftereffects, however, was independent from both skin properties and tactile abilities; suggesting that the underlying cortical processes are rather robust and stable. Interindividual variability in the aftereffect magnitude might instead stem from e.g. cortical idiosyncrasies causing differences in the susceptibility to neural adaptation. For active touch, we examined in the third study if and how prior visual information can be exploited for texture exploration. Participants had to discriminate grating textures by spatial frequency while receiving prior visual cues of varying quality about texture orientation. These priors influenced exploratory movement direction similarly to adjustments known to emerge during exploration and to enhance perception, but notably, they did so already at initial contact. The degree of adjustment scaled with the quality, i.e. informational value of the priors, consistent with established motor control models. The findings show that humans can flexibly learn to use abstract visual priors to optimize haptic explorations, with the learning process and direct usage substantially depending on the priors’ quality. In the fourth study, we corroborated and extended findings from study 3 with an investigation in a more naturalistic VR-setting, assessing haptic exploration of real-life materials (sand, sponge, sandpaper), and how naturalistic prior visual information affects the initial movement selection beyond single movement parameter adjustment but with regard to holistic movement selection. Results showed that with adequate prior visual information, participants explored materials in a more efficient way: they used specialized exploratory procedures earlier, with higher probability, and explored materials for a shorter time. In the fifth study, we assessed factors that humans might take into account for termination of exploratory behavior. (Expected) task demands are known to influence, e.g., force tuning in softness exploration. Exploration extension generally improves discrimination performance up to a saturation point. We therefore hypothesized that humans adjust exploration durations according to current task demands and assessed this in a haptically rendered grating discrimination task. However, exploration extension increases motor costs, which humans typically seek to minimize; to examine the role of motor costs for haptic explorations, we artificially manipulated motor effort by implementing counteracting forces in a force-feedback device. Results showed that increased task demands were compensated by exploration extension, but the extent of this compensation depended on the motor costs the agent was confronted with. This likely reflects the agent’s dynamically updated cost-benefit expectations. Altogether, this dissertation provides new behavioral evidence on how efficiency of touch perception is supported by robust early cortical mechanisms jointly encoding different tactile features, as well as higher-level prediction processes that enable exploratory movement adjustments for optimized sensory data gathering.
Keywords: Perceptual efficiency; Haptic exploration; Visual guidance; Perceptual efficiency; ddc:150